A benign teratoma of the ovary fistulating into the rectum - Wickramasinghe, D; Samarasekera, D. N. (The Sri Lanka Medical Association, 2010)
In Greek, teratoma means "monstrous tumour". Teratomas account for 10-20% of all ovarian neoplasms. More than 95% are benign (dermoid cysts). Less than 2% of cystic lesions contain malignant tissue, while more than 80% of solid teratomas are malignant.
Keywords: teratoma